Development of Alphabet Word Card Media on Thematic Learning for Elementary School Students - Faralia, Dina; Basri, Amin (research, training and philanthropy institution Natural Aceh, 2024)
This research aims to develop learning media for alphabet word cards in thematic learning theme 3,